Gambaran Tingkat Risiko Penyakit Kardiovaskular - Abel Aprilia Malingkonor; Nanang Roswita Paramata; Ibrahim Suleman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the level of cardiovascular disease risk at the Limboto Community Health Center in Gorontalo Regency. The method used was quantitative descriptive with a cross-sectional design. The results showed that the majority of respondents were in the low-risk category (44 respondents (66.7%), followed by 11 respondents (16.7%) at moderate risk, 6 respondents (9.1%), and 5 respondents (7.6%) at very high risk, with no respondents in the high-risk category. In conclusion, the majority of Prolanis participants at the Limboto Community Health Center have a low risk of cardiovascular disease, but there are still moderate to very high risk groups that require ongoing attention and preventive intervention. Keywords: Diabetes Mellitus, Risk Factors, Hypertension, Cardiovascular Disease, WHO/ISH Non-Laboratory Risk Prediction Chart (SEAR B)